Epigenetic Priming in Immunodeficiencies - Martínez-Cano, Jorge; Campos-Sánchez, Elena; Cobaleda, César (Frontiers in Cell and Developmental Biology, 2019)
Immunodeficiencies (IDs) are disorders of the immune system that increase susceptibility to infections and cancer, and are therefore associated with elevated morbidity and mortality. IDs can be primary (not caused by other condition or exposure) or secondary due to the exposure to different agents (infections, chemicals, aging, etc.). Most primary immunodeficiencies (PIDs) are of genetic origin, caused by mutations affecting genes with key roles in the development or function of the cells of the immune system. A large percentage of PIDs are associated with a defective development and/or function of lymphocytes and, especially, B cells, the ones in charge of generating the different types of antibodies. B-cell development is a tightly regulated process in which many different factors participate. Among the regulators of B-cell differentiation, a correct epigenetic control of cellular identity is essential for normal cell function. With the advent of next-generation sequencing (NGS) techniques, more and more alterations in different types of epigenetic regulators are being described at the root of PIDs, both in humans and in animal models. At the same time, it is becoming increasingly clear that epigenetic alterations triggered by the exposure to environmental agents have a key role in the development of secondary immunodeficiencies (SIDs). Due to their largely reversible nature, epigenetic modifications are quickly becoming key therapeutic targets in other diseases where their contribution has been known for more time, like cancer. Here, we establish a parallelism between IDs and the nowadays accepted role of epigenetics in cancer initiation and progression, and propose that epigenetics forms a “third axis” (together with genetics and external agents) to be considered in the etiology of IDs, and linking PIDs and SIDs at the molecular level. We therefore postulate that IDs arise due to a variable contribution of (i) genetic, (ii) environmental, and (iii) epigenetic causes, which in fact form a continuum landscape of all possible combinations of these factors. Additionally, this implies the possibility of a fully epigenetically triggered mechanism for some IDs. This concept would have important prophylactic and translational implications, and would also imply a more blurred frontier between primary and secondary immunodeficiencies.